Broberg and Fenger on preliminary references to the European Court of Justice - Broberg, Morten P.; Fenger, Niels, 1968- (Oxford : Oxford University Press, 2021)
This text is structured to reflect the different questions that may arise in connection with a preliminary reference. It explains who can make a reference, what questions can be referred, and when can, when should, and when must a reference be made. Thereupon the book provides detailed guidance on the form and contents of the actual reference as well as the procedure, both before the referring court and the European Court of Justice.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 22, 2021).
Keywords: Court of Justice of the European Communities; Procedure (Law) -- European Union countries; Reference legislation -- European Union countries